Os desafios do crime cibernético - Herman, Susan N. (Revista Eletrônica de Direito Penal e Política Criminal, 2013)
The article presents an overview of the computer crimes in the light of American law. Therefore, it examines the main normative acts elaborated in the United States regulating the matter, as well as high-profile cases that were the subject of criminal prosecution. Finally, some problems are examined and is made a critical remark.